Expanding biodiversity conservation beyond the official mandate of the Dwesa-Cwebe nature reserve of South Africa : qualitative assessment based on Nqabara administrative area - Mungatana, Eric D. (University of Pretoria, 2013)
Dissertation (MInstAgrar)--University of Pretoria, 2010.